Correlation between Skip N2 Metastases and SUVmax, Long Diameter of Tumor, and Ki67 Expression in Patients with Non-Small-Cell Lung Cancer. (27th April 2020) - Jian, Wang; Ming-ya, Peng; Long-bao, Xu; Jun, Zhao; Guo-qiang, Shao
Abstract : Background . We aim at investigating the correlation between skip N2 metastases (SN2) and SUVmax, long diameter of tumor mass after 18 F-FDG PET/CT, and pathological Ki67 expression in patients with non-small-cell lung cancer (NSCLC). Methods and Results . We retrospectively analyzed the factors that might affect the pathogenesis of SN2 in these patients. The clinical SN2 symptoms in patients with squamous carcinoma or adenocarcinoma were investigated. The work curve was utilized to analyze the optimal cutoff value for the SUVmax and long diameter of tumor. Multivariate analysis revealed that high expression of Ki67 was a risk factor for mediastinal SN2 (OR = 1.042, 95% CI: 1.009-1.076). Subgroup analysis indicated that the SUVmax of the non-SN2 group was significantly higher than that of the SN2 group in patients with squamous carcinoma (16.3 ± 6.0 vs. 10.7 ± 5.6, P = 0.026 ). In the patients with adenocarcinoma, the long diameter of tumor in the SN2 group was significantly longer than that of the non-SN2 group (43.8 ± 16.3   mm vs. 30.1 ± 13.8   mm, P = 0.032 ). The Ki67 expression in the SN2 group was significantly higher than that of the non-SN2 group (51.7 ± 24.0 vs. 30.0 ± 19.2, P = 0.028 ). Conclusions . The differences of clinical features of the patients in the SN2 group and non-SN2 group in the NSCLC patients were associated with the pathological subtypes, which were featured by lower SUVmax in the SN2 of the squamous carcinoma, and longer diameter of SN2 in the adenocarcinoma patients.